Total synthesis of (±)-erythrodiene and (±)-spirojatamol. (23rd November 2021) - Cheng, Fu; Duan, Dong-Sen; Zhang, Ye; Zheng, Tian-Lu; Zhang, Xiao-Yun; Wang, Shao-Hua; Xu, Xue-Tao; Zhu, Dao-Yong
Graphical abstract: Highlights: A unique synthetic strategy toward (±)-erythrodiene and (±)-spirojatamol has been achieved. A tandem coupling/1, 3-shift/1, 2-rearrangement sequence was used to construct the key skeleton. The synthesis of (±)-erythrodiene and (±)-spirojatamol was achieved via an 11-step route. Abstract: A unique synthetic strategy toward (±)-erythrodiene and (±)-spirojatamol was achieved from cyclobutone and isobutyraldehyde through an 11-step synthetic route. During the work, a tandem Castro-Stephens coupling/1, 3-acyloxy shift/cyclization/semipinacol rearrangement sequence, which was developed recently by the same group, was used as the key step to build the crucial spirocyclic intermediate 5b .